Prevalence of leisure participation in older adults with and without pain: A secondary data analysis of the 2014 Health and Retirement Study. (June 2022) - Feller, Haley; Baker, Nancy
Objectives: The purpose of this study is to describe the prevalence of leisure activities in adults ages 50 and over and to examine if pain changes that prevalence. Methods: We completed a secondary analysis using data from the 2014 Health and Retirement Study Leave-Behind Questionnaire (n = 7, 541) to analyze frequency and 95% confidence intervals of leisure participation and its relationship to pain. Results: The majority of respondents reported regular participation in half of the 10 leisure activities analyzed. Watching television (98.0%) and using the computer (64.5%) had the highest reported regular participation, while volunteering and attending a club or meeting warranted less than 10% regular participation. Of the 7, 541 respondents, 39.1% reported pain. For those with pain, regular participation was significantly lower than those without pain in five leisure activities, with exercise having the greatest difference. Discussion: The results of our secondary data analysis indicate that older adults may not be regularly participating in different types of leisure activities and that they more regularly participate in passive activities, such as watching television. Older adults with pain have significantly lower reported rates of participation in leisure activities than those without pain, especially in relation to exercise.